Convenient One‐Pot Synthesis of 1, 2, 3, 4‐Thiatriazoles Towards a Novel Electron Acceptor for Highly‐Efficient Thermally‐Activated Delayed‐Fluorescence Emitters. Issue 10 (25th January 2019) - Qu, Yangyang; Pander, Piotr; Bucinskas, Audrius; Vasylieva, Marharyta; Tian, Yayang; Miomandre, Fabien; Dias, Fernando B.; Clavier, Gilles; Data, Przemyslaw; Audebert, Pierre
Abstract: A novel and unexpected convenient one‐pot synthesis of 1, 2, 3, 4‐thiatriazoles has been discovered while investigating the classical tetrazine "Pinner synthesis". The synthetic route starts from commercially‐available nitrile derivatives and gives good to high yields (51–80 %) with no need to isolate any thioacylating agents. The crucial impact of the solvent on the outcome of the modified "Pinner synthesis" is moreover examined and discussed. Using this new synthetic route, a novel donor‐acceptor thiatriazole derivative has been prepared, which exhibits prominent thermally‐activated delayed fluorescence (TADF) in both solution and film. The photoluminescence quantum yield (PLQY) in methylcyclohexane (MCH) and Zeonex (a cyclo olefin polymer) in oxygen‐free conditions were determined to be 76 and 99 %, respectively. This work provides an efficient and practical synthetic approach to functionalized 1, 2, 3, 4‐thiatriazole derivatives, and will noticeably facilitate the application of 1, 2, 3, 4‐thiatriazole as an electron acceptor in organic electronics. Abstract : One‐stop shop : A novel and unexpected convenient one‐pot synthesis of 1, 2, 3, 4‐thiatriazoles has been discovered meanwhile investigating on the classical tetrazine "Pinner synthesis". The synthetic route starts from commercially‐available nitrile derivatives and gives good to high yields (51–80 %) with no need to isolate any thioacylating agents. Using this new synthetic route a novel donor‐acceptor thiatriazole derivative has been prepared which exhibits prominent thermally activated delayed fluorescence (TADF).